2023
DOI: 10.59717/j.xinn-geo.2023.100038
|View full text |Cite
|
Sign up to set email alerts
|

Human-environment interaction systems between regional and continental scales in mid-latitude Eurasia during 6000�C3000 years ago

Guanghui Dong,
Linyao Du,
Ruiliang Liu
et al.

Abstract: <p>The Late Neolithic and Bronze Ages witnessed the extensive expansion of human settlements, along with the dispersal of crops and livestock originating from West and East Asia. These events profoundly reshaped the human-environment relationship in mid-latitude Eurasia and the underlying trans-Eurasian exchange. While the processes and factors that underpin the interaction between human societies and ever-changing environments have been a heated debate in various regions of Eurasia, there is still a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The model results offer an objective but somewhat bland perspective, and it is crucial to interpret them in conjunction with practical archaeology. Previous studies have proposed several perspectives primarily focused on socioeconomic and climatic changes [24,28,35,36,114,115]. In the present study, we further analyzed this process by quantitively analyzing subsistence and climate dynamics across three cultural periods.…”
Section: Socioeconomic and Climatic Changes Explain Settlements Dynam...mentioning
confidence: 97%
See 1 more Smart Citation
“…The model results offer an objective but somewhat bland perspective, and it is crucial to interpret them in conjunction with practical archaeology. Previous studies have proposed several perspectives primarily focused on socioeconomic and climatic changes [24,28,35,36,114,115]. In the present study, we further analyzed this process by quantitively analyzing subsistence and climate dynamics across three cultural periods.…”
Section: Socioeconomic and Climatic Changes Explain Settlements Dynam...mentioning
confidence: 97%
“…Previous discussions, which primarily relied on GIS visualization and spatial analysis, have demonstrated that social subsistence in the NETP heavily influenced settlement distribution patterns during different cultural periods [33][34][35]. On the other hand, trans-continental cultural exchange and climate fluctuation served as underlying factors in shaping societal patterns [34][35][36]. Many studies have explored these perspectives and proposed more factors influencing human activities, including hydrological, topographical, and vegetation factors.…”
Section: Introductionmentioning
confidence: 99%